2016
DOI: 10.1103/physrevfluids.1.064302
|View full text |Cite
|
Sign up to set email alerts
|

Near isotropic behavior of turbulent thermal convection

Abstract: We investigate the anisotropy in turbulent convection in a 3D box using direct numerical simulation. We compute the anisotropic parameter A = u 2 ⊥ /(2u 2 ), where u ⊥ and u are the components of velocity perpendicular and parallel to the buoyancy direction, the shell and ring spectra, and shell-to-shell energy transfers. We observe that the flow is nearly isotropic for the Prandtl number Pr ≈ 1, but the anisotropy increases with the Prandtl number. For Pr = ∞, A ≈ 0.3, thus anisotropy is not very significant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…For such experiments, the Taylor's hypothesis [56,94,105] is invoked to relate the frequency power spectrum E( f ) of the time series to the one-dimensional wavenumber spectrum E k ; ( ) this connection is under debate due to the absence of any constant mean velocity field [56,63]. Researchers [57,104,122,123] employ 2D particle image velocimetry for high-resolution visualization and computation of an approximate energy spectrum under the assumption of homogeneity and isotropy, which is not strictly valid in convection [75]. In summary, on the experimental front, there is no convergence on which of the two scaling, BO of KO, is valid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For such experiments, the Taylor's hypothesis [56,94,105] is invoked to relate the frequency power spectrum E( f ) of the time series to the one-dimensional wavenumber spectrum E k ; ( ) this connection is under debate due to the absence of any constant mean velocity field [56,63]. Researchers [57,104,122,123] employ 2D particle image velocimetry for high-resolution visualization and computation of an approximate energy spectrum under the assumption of homogeneity and isotropy, which is not strictly valid in convection [75]. In summary, on the experimental front, there is no convergence on which of the two scaling, BO of KO, is valid.…”
Section: Resultsmentioning
confidence: 99%
“…Convective flows are expected to be anisotropic due to buoyancy; hence it is important to quantify anisotropy using the quantities that are dependent on the polar angle, the angle between zˆand k. For the same, we divide a wavenumber shell into rings [75]. The energy contents of the rings are called ring spectrum b E k, ( ), where β represents the sector index for the polar angles (for details see Nath et al [75]). The ring spectrum b E k, ( ), depicted in figure 9(b), shows that the flow is nearly isotropic, again similar to hydrodynamic turbulence.…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…Velocity structure functions of turbulent convection Sun, Zhou, and Xia 25 and Zhou, Sun, and Xia 53 performed experiments of turbulent thermal convection and observed isotropy in regions away from walls. Using detailed numerical simulations, Nath et al 52 computed the modal energy of the inertial-range Fourier modes of turbulent convection as a function of polar angle Θ (angle between buoyancy direction and the wavenumber), and found it to be approximately independent of Θ. Thus, they showed that turbulent convection is nearly isotropic.…”
Section: Nowmentioning
confidence: 99%
“…Another major feature of Tarang is its rich library for computing the energy transfers in turbulence, e.g., energy flux, shell-to-shell and ring-to-ring energy transfers, etc. [18,35,21]. Tarang also enables us to probe any point in the Fourier space or in the real space [28].…”
Section: Introductionmentioning
confidence: 99%